Afrodescendentes nas fotografias de Lunara : representação imagética em um sistema cultural hegemônico - Teixeira, Teresinha de Castro (2022)
This research aims to interpret a series of photographs of Afro-descendants by Luiz do Nascimento Ramos (1864-1937), known as Lunara, merchant and amateur photographer. The historical context in which the images were produced is that of the First Republic, after the abolition of slavery, in Porto Alegre during the 1910s. The research problem relates Lunara's photographic series to the broader issue of forms of representation of different social groups through the subordination of black people, the disqualification of their work, the restriction of their rights and political citizenship. For this, the images of Afro-descendants portrayed in relation to the socio-historical and visual context of the time were analyzed, in dialogue with studies on multicultural issues. The research puts the series of photographs in temporal perspective, relating them to the imagery representations of traveling artists, during the colonial period, passing through the first photographs of blacks still slaves and reaching the post-abolition period in Lunara's time. The analysis is guided by the continuity of discriminatory cultural representations of minorities in the Brazilian cultural imagery system, especially of black people in the context of social modernization at the beginning of the Republic. The study also raises questions about how imagery representations become constructors and legitimizers of differences, subordination and social exclusion of minorities.